(untitled) (Educação e Pesquisa, 2001)
This article examines the theoretical assumptions and empirical findings of three discrete perspectives guiding research on adult literacy. These perspectives are: literacy as a decontextualized basic skill, literacy as a social practice embedded in local conditions, and literacy as a tool for individual and collective empowerment, especially for the empowerment of women. Divergence exists along several lines: the conception of literacy, the imputed potential of literacy to contribute to national development and modifying social conditions, the potential for a valid standardized measurement of literacy skills, the role of mediators in the processing of print literacy, and to the power of context to determine the possibility of literacy to becoming a stable practice. Convergence exists when considering literacy programs difficult to implement and in great need of long-term political commitment, adequate teacher training, and financial resources appropriate for the expressed literacy objectives. From the perspective of womens empowerment, the content of literacy messages and participatory learning methodologies in literacy programs, as well as the need for multisectoral support, is crucial. Iliteracy rates are slowly decreasing throughout the world, but the absolute number of those unable to read or write is increasing. Persistently, women comprise two-thirds of the illiterates. Current poverty conditions and the mechanisms in place to counter their manifestations work against the participation of learners in literacy programs and their subsequent application of literacy skills to everyday life. The article is based on a review of the recent literature on adult literacy, most of which has appeared in books and journals in English.